The Third Reich's intelligence services the career of Walter Schellenberg - Paehler, Katrin (Cambridge University Press, 2017)
"This is the first-ever analytical study of Nazi Germany's political foreign intelligence service, Office VI of the Reichssicherheitshauptamt and its head, Walter Schellenberg. Katrin Paehler tells the story of Schellenberg's career in policing and intelligence, charts the development and activities of the service he eventually headed, and discusses his attempts to place it at the center of Nazi foreign intelligence and foreign policy. The book locates the service in its proper pedigree of the SS as well as in relation to its two main rivals - the Abwehr and the Auswärtige Amt. It also considers the role Nazi ideology played in the conceptualization and execution of foreign intelligence, revealing how this ideological prism fractured and distorted Office VI's view of the world. The book is based in contemporary and postwar documents - many recently declassified - from archives in the United States, Germany, and Russia."--Provided by publisher
Gaining a foothold -- Rising star -- Intelligence man -- Office VI and its forerunner -- Competing visions: Office VI and the Abwehr -- Doing intelligence: Italy as an example -- Alternative universes: Office VI and the Auswartige Amt -- Schellenberg, Himmler, and the quest for "peace" -- Postwar
Keywords: Schellenberg, Walter / 1910-1952; Nationalsozialistische Deutsche Arbeiter-Partei / Schutzstaffel / Reichssicherheitshauptamt; Nationalsozialistische Deutsche Arbeiter-Partei / Schutzstaffel / Sicherheitsdienst; Nationalsozialistische Deutsche Arbeiter-Partei / Schutzstaffel / Biography; Weltkrieg (1939-1945); World War, 1939-1945 / Secret service / Germany; Nazis / Biography; Intelligence officers / Germany / Biography; Deutschland; Biografie